Transformasi Pembelajaran Matematika Berbasis Problem Based Learning (PBL) untuk Menurunkan Mathematics Anxiety Siswa - Tyaningsih, Ratna Yulis; Junaidi, Junaidi; Lu'luilmaknun, Ulfa (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Mathematics anxiety is a psychological barrier that can hinder students’ academic achievement, particularly in mathematics learning. This anxiety disrupts concentration, reduces self-confidence, and often leads to low learning outcomes. This study aimed to examine the effectiveness of the Problem Based Learning (PBL) approach in reducing mathematics anxiety among seventh-grade students on the topic of Social Arithmetic. A quasi-experimental method with a pre-intervention and post-intervention control group design was employed. The research subjects consisted of seventh-grade students at SMPN 20 Mataram, selected through purposive random sampling. The instrument used was a modified Mathematics Anxiety Rating Scale (MARS) adapted for junior high school context. Data were analyzed using normality and homogeneity tests, independent sample t-test, and N-Gain score calculation. The results indicated that students who received PBL-based instruction experienced a significantly greater reduction in mathematics anxiety than those who received conventional instruction, as shown by the t-test result (p = 0.000 < 0.05). Furthermore, the experimental group achieved an N-Gain score of 0.65, categorized as moderate, suggesting that the PBL approach substantially enhanced the reduction of mathematics anxiety. These findings affirm that PBL not only improves students’ understanding of Social Arithmetic but also has a positive impact on their affective learning domain. The implication of this study emphasizes the importance of transforming mathematics instruction toward more contextual, collaborative, and student-centered approaches to create more comfortable and meaningful learning experiences.